2017
DOI: 10.1002/14651858.cd012226.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve adherence to inhaled steroids for asthma

Abstract: Pooled results suggest that a variety of interventions can improve adherence. The clinical relevance of this improvement, highlighted by uncertain and inconsistent impact on clinical outcomes such as quality of life and asthma control, is less clear. We have low to moderate confidence in these findings owing to concerns about risk of bias and inconsistency. Future studies would benefit from predefining an evidence-based 'cut-off' for acceptable adherence and using objective adherence measures and validated too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
105
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 112 publications
2
105
1
5
Order By: Relevance
“…Methods of adherence reporting also varied between studies, which limited direct comparisons between studies. The average adherence of the studies which reported percentage adherence in our review was 48%, which reflects the typical rates reported in asthma adherence literature [84,85] (usually estimated to be ∼50%). Whilst this supports the generalisability of our findings to most asthma populations, they may not be applicable to populations with very poor adherence.…”
Section: Limitationssupporting
confidence: 77%
“…Methods of adherence reporting also varied between studies, which limited direct comparisons between studies. The average adherence of the studies which reported percentage adherence in our review was 48%, which reflects the typical rates reported in asthma adherence literature [84,85] (usually estimated to be ∼50%). Whilst this supports the generalisability of our findings to most asthma populations, they may not be applicable to populations with very poor adherence.…”
Section: Limitationssupporting
confidence: 77%
“…This suggests that we cannot assume interventions will be effective in young adults and require formal evaluations. Similarly, there is evidence from a systematic review that education, electronic trackers/reminders, and simplified regimens result in better medication adherence among asthmatic patients than control interventions (31). Interventions can also positively influence social outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with a recent Cochrane review of interventions targeting adherence to inhaled corticosteroids. The review found a significant intervention effect on adherence when compared to usual care [44]. In terms of intervention location, previous research looking at pharmaceutical care activities and resources across Europe also found significant differences between countries [45].…”
Section: Discussionmentioning
confidence: 75%
“…We did not analyse data for asthma control, the most common primary outcome. However, it was felt that a review of data on adherence to asthma medication and subsequent asthma control was covered in a recent Cochrane review, so we did not duplicate this [44]. The guidelines for a small, medium and large effect size (d) do not translate directly into the healthcare realm.…”
Section: Limitations Of Included Studiesmentioning
confidence: 99%